Dental odyssey: a comprehensive literature review on global strategies, behavioral programs, and creative approaches for ages 6-12 years - Meysa Ayu Cahyani; Agus Sudaryanto (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2024)
Introduction: Oral and dental hygiene serves as an indicator of a condition free from diseases, debris, and health issues in the oral cavity, affecting individuals of all age groups. Health education through various global learning systems, behavioral programs, and creative approaches has proven effective in enhancing children's understanding of the importance of maintaining oral and dental cleanliness. Objective: Objective: This research aims to review relevant journals contributing to the development of insights, behaviors, and understanding regarding children's oral and dental health across crucial age ranges. Methods: Using a literature review method, we filtered articles from Google Scholar, PubMed, Garuda (Digital Reference Library), and Science Direct published within the last six years. Searches in both Indonesian and English languages yielded ten articles that, after a selection process, provided diverse results regarding the implementation of learning models to enhance children's understanding of their oral and dental hygiene. Result: From the ten articles, it can be concluded that the application of education on oral and dental hygiene through various learning systems can effectively improve children's knowledge. Conclusion: the oral hygiene of elementary school children from various countries. Variations in research designs were found, and there is low awareness among children regarding dental health in Indonesia. Educational programs, such as